Increasing Opportunities to Respond for Students With Internalizing Behaviors: The Utility of Choral and Mixed Responding. (August 2017) - Messenger, Mallory; Common, Eric Alan; Lane, Kathleen Lynne; Oakes, Wendy Peia; Menzies, Holly Mariah; Cantwell, Emily D.; Ennis, Robin Parks
Increasing students' opportunities to respond (OTR) is a low-intensity strategy effective in increasing engagement. Building on the work of Haydon and colleagues, we compared two types of OTR, choral and mixed (70% choral, 30% individual), to examine the utility of these strategies in increasing active student responding and accuracy during mathematics for two elementary-age students with internalizing behaviors. Results indicated the general education teacher implemented both OTR strategies with high fidelity with limited university support. However, results of this alternating treatment design were unable to distinguish either choral or mixed responding as superior to the other. Results suggested one student showed high active student responding with less than 80% accuracy, whereas the other student was highly accurate but responded less than 75% of the time. In the discussion, we highlight reasons why the two OTR strategies had similar effects on student outcomes, consider implications of these findings, and provide direction for future inquiry.